Contribuições científicas em pedagogia empresarial: um estudo sobre atuação do pedagogo nas instituições - CAVALHEIRO, Brenda Suellen Dias (2022)
This work was completed aiming to know the contributions about the subject of business pedagogy in aspects that mainly affect the professional performance, besides adding other relevant points such as the importance of its performance and the difficulties faced for its placement in the labor market, taking into account the main changes occurred in the management of people in the business environment with the advent of the so-called Era of Knowledge. To study this performance, the research had the analysis of three specific works in the theme, besides a regional research seeking to understand how this professional insertion takes place. The results were satisfactory to the objectives, it was possible to understand that this professional performance is not dissociated from the educational character and seeks primarily to train and develop the employees, besides offering a healthier environment within the corporations. However, it is possible to conclude that the performance of the business pedagogy is of great relevance in the organizational environment where improvements are sought through the intellectual capital of its employees, which is the most valuable capital in the current Age of knowledge.